Who Cares?: Improving collection of childcaring responsibilities of postgraduate students in UK higher education - Davis, Billy; Beck, Alice (International Journal of Population Data Science, 2025)
Objectives As part of GW4 (the University Alliance for the universities of Bath, Bristol, Cardiff and Exeter)’s ongoing postgraduate childcare campaign, our research will explore the lack of consistent administrative data and how this hinders properly assessing the size and needs of this cohort. Method GW4 will work with universities across the United Kingdom to understand the kind of administrative data that institutions currently collect on the childcaring needs of postgraduates, the reason why they collect this data, and ways in which administrative systems could be improved in order to ensure data is captured in a more uniform way across institutions. This will largely use qualitative research methods – including interviews, Freedom of Information Requests and other forms of correspondence. Results At the time of submission, the results of this study are still pending. However, we anticipate to have some preliminary results ahead of the September Conference, which we will include in our poster. Conclusions As above, conclusions of the final study are still pending. We will use the recommendations to build on the policy recommendations of GW4’s policy paper “Who cares? How postgraduate parents fall through the gap for government childcare grants, and how to fix it”, which called for the Higher Education Statistics Agency (HESA) to work with universities to improve data collection on postgraduate students with childcare responsibilities. Our recommendations will work to ensure that administration staff gather data in a more universal way, allowing higher education institutions and policymakers to better understand the size and needs of this cohort.